The insertion of Globo Filmes in the Brazilian cinematographic scene - Dantas, Guibson (2018)
Institutions, demonstrations, and socio-cultural movements; disputes, interests and power games; relations with the State, positions, and discursive formations, are some nuances that demarcate the trajectory of Brazilian cinema. In this wake, we turn our attention to the insertion of Globo Filmes in the national cinematographic scene. To this end, the study encompasses the contextualisation of the economic transformations of this context, with emphasis on the creation of the company under consideration, and in the years subsequent to such event (1998-2007). Understanding the contours of Brazilian cinema, considered here the relations with television, are the guiding threads of this text.